Impact of unconditional cash transfer on civil conflict - KENNETH, Onyango (KDI School, 2016)
The study aims to contribute to existing research on utilization of unconditional cash transfers (UCT) in improving the economic wellbeing of conflict prone disenfranchised communities. It analyzed the use of UCT in promoting business start-ups that enhances access to economic resources through employment creation and thus deters membership to insurgent groups. The analysis exploited data obtained from randomized control experiment conducted by the Hunger and Safety Net Program (HSNP) during the period 2009 to 2014. The HSNP delivered regular UCT to households in the conflict prone region of Northern Kenya. Data on conflict was obtained from an independent source maintained by Armed Conflict Location and Event Data Project (ACLED). The summary statistics from regression analysis shows that UCT had statistically significant impact in reducing incidences of conflict. In addition, the difference in difference analysis showed substantial reduction in annual average number of conflicts in the treatment sub-locations compared to incidences reported in the control locations. The cash transfer also caused substantial increase in self-employment as recipients opted to start businesses. The business start-ups created jobs thereby reducing attractiveness of joining insurgency groups or participating in conflict.
Thesis(Master) --KDI School:Master of Development Policy,2016